THE IMPORTANCE OF USE OF EFFECTIVE SENTENCES FOR PHYSICAL STUDENTS OF UNIMED FMIPA - Halimatussakdiah Halimatussakdiah (JURNAL HANDAYANI PGSD FIP UNIMED, 2018)
Abstract : The Importance of Effective Use of Sentences for Physics Students of UNIMED FMIPA. This study aims to determine the importance of using effective sentences for students. The type of this research is descriptive qualitative with the subject of the study are 15 students of the 2014 class D physics class D education program. The technique of collecting data using test instruments amounted to 15 questions and analyzed with descriptive techniques. The results of this study state that the understanding of Physics students on the use of effective sentences is 40% on very good criteria, 33.33% criteria are good, 13.33% criteria are sufficient and less. The conclusion of this study is that students' understanding of efketif sentences is classified as moderate.Keywords : Effective SentencesAbstrak : Pentingnya Penggunaan Kalimat Efektif Bagi Mahasiswa Fisika FMIPA UNIMED. Penelitian ini bertujuan untuk mengetahui pentingnya penggunaan kalimat efektif bagi mahasiswa. Jenis penelitian ini adalah deskriptif kualitatif dengan subjek penelitian adalah 15 mahasiswa program studi pendidikan fisika kelas D stambuk 2014. Teknik pengumpulan data dengan menggunakan instrumen tes berjumlah 15 soal dan dianalisis dengan teknik deskriptif. Hasil penelitian ini menyatakan bahwa pemahaman mahasiswa Fisika terhadap penggunaan kalimat efektif sebesar 40% pada kriteria sangat baik, 33,33% kriteria baik, 13,33% kriteria cukup dan kurang. Kesimpulan dari penelitian ini adalah pemahaman mahasiswa terhadap kalimat efketif tergolong sedang.Kata Kunci : Kalimat Efektif